Impact of Prior Clinical Information in an EHR on Care Outcomes of Emergency Patients - Theera-Ampornpunt, Nawanan (American Medical Informatics Association, 2009)
A patient’s prior clinical information available electronically can be helpful during the care process, particularly in the emergency department (ED). The effect of such information on quality and efficiency of ED patient care has not been adequately studied. This study uses secondary data to investigate its impact on surrogate measures of care quality and efficiency among 6,143 congestive heart failure, diabetic, and asthmatic patients in 3 EDs. Results show that in some subgroups of chronic patients in some EDs, availability of prior clinical information in the electronic health records was associated with significantly lower hospitalization rates, shorter inpatient length of stay, and reduction in the numbers of laboratory tests and diagnostic procedures ordered during the ED visit. However, there were also contradictory effects and lack of significance in other subgroups. The effects vary by ED and disease, highlighting the possibility of contextual differences influencing the effects of such clinical information.